Costs and consequences of different chemotherapy regimens in metastatic colorectal cancer. - Hale, J; Cohen, DR; Maughan, T; Stephens, R (2002)
An economic sub-study was run alongside a large multi-centre randomised trial (MRC-CR06) comparing three chemotherapy regimens; de Gramont, Lokich and raltitrexed in patients with metastatic colorectal cancer. Patients in six of 45 centres in the main trial were approached to take part in the sub-study. Chemotherapy delivery costs were assessed in each sub-study centre with external validity verified by questionnaire to all other centres. Patient representativeness was assessed. Stochastic resource use data, including patient borne costs and non-hospital health service resource use were monitored prospectively. Mean total societal costs were de Gramont= 5051 pounds sterling (s.d. 1910 pounds sterling ), raltitrexed= 2616 pounds sterling (s.d. 991 pounds sterling ) and Lokich= 2576 pounds sterling (s.d. 1711 pounds sterling ). In pairwise comparisons, statistically significant mean total cost differences were shown for de Gramont vs Lokich (mean difference= 2475 pounds sterling , 95%CI 914 pounds sterling - 4037 pounds sterling , P<0.01) and for de Gramont vs raltitrexed (mean difference= 2435 pounds sterling, 95%CI 922 pounds sterling - 2948 pounds sterling , P<0.01). Sensitivity analyses showed little effect on overall costs. The main trial showed de Gramont and Lokich to be equally effective in terms of survival, quality of life and response rates but Lokich had higher toxicity and hand-foot syndrome. Raltitrexed showed similar response rates and overall survival but increased toxicity and inferior quality of life making it a clinically inferior regimen despite its ease of administration and costs. For a comparable clinical outcome, Lokich can be administered for approximately half the cost of de Gramont.